A discourse analysis of news items on fire warning in English and Vietnamese - Trương, Thị Thanh Phương. (The University of Da Nang, 2014)
This study makes an investigation into English New Items on Fire Warning (ENFW) and Vietnamese New Items on Fire Warning (VNFW) in order to discover some typical discourse features and find out the similarities and differences between them in terms of the layout, lexical features, syntactic structures and cohesive devices. The research has been conducted based on the combination of the descriptive method and the contrastive one.This study is based on a survey of 50 news items in English and Vietnamese newspapers which are taken from well-known websites for six recent years from 2009 to 2014. The findings show that along with some similarities, there are a number of noticeable differences. Based on the paper “Warning as Framing: discourse competition in the European security sphere” (Chiara de Franco, 2010) in terms of layout, ENFW and VNFW consist of five components: headline, warner, addressee future harm, and policy recommendation. In terms of lexical choices, there are the verbs commonly used in fire warnings. With regard to the syntactic features, direct and indirect speeches, comparative and imperative sentences are investigated. For the cohesive devices, the thesis studies both lexical cohesion and grammatical cohesion. It is hoped that the results of the study will serve as an access for profound understanding of fire warnings in English. The study can be a reference that helps to improve the reading and writing skills of fire warnings for English learners.